2022
DOI: 10.3389/fped.2022.926013
|View full text |Cite
|
Sign up to set email alerts
|

Increased Severe Cases and New-Onset Type 1 Diabetes Among Children Presenting With Diabetic Ketoacidosis During First Year of COVID-19 Pandemic in Turkey

Abstract: IntroductionThere have been some significant changes regarding healthcare utilization during the COVID-19 pandemic. Majority of the reports about the impact of the COVID-19 pandemic on diabetes care are from the first wave of the pandemic. We aim to evaluate the potential effects of the COVID-19 pandemic on the severity of diabetic ketoacidosis (DKA) and new onset Type 1 diabetes presenting with DKA, and also evaluate children with DKA and acute COVID-19 infection.MethodsThis is a retrospective multi-center st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“… 17 It was stated that in the first year of the pandemic in Turkey, the frequency of cases admitted to pediatric intensive care units (27 centers) across the country due to severe DKA increased compared to the previous year (70.2% vs. 56.5%). 18 However, it is also stated that this study cannot clearly show the frequency of DKA in all newly diagnosed diabetics, as hospitalizations of wards or admissions with hyperglycemia were not evaluated. 18 In another study where the frequency of DKA was evaluated in the first year of the pandemic in Turkey compared to the previous year, the frequency of severe DKA among hyperglycemia, ketosis, and ketoacidosis admissions was found to be 23%.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“… 17 It was stated that in the first year of the pandemic in Turkey, the frequency of cases admitted to pediatric intensive care units (27 centers) across the country due to severe DKA increased compared to the previous year (70.2% vs. 56.5%). 18 However, it is also stated that this study cannot clearly show the frequency of DKA in all newly diagnosed diabetics, as hospitalizations of wards or admissions with hyperglycemia were not evaluated. 18 In another study where the frequency of DKA was evaluated in the first year of the pandemic in Turkey compared to the previous year, the frequency of severe DKA among hyperglycemia, ketosis, and ketoacidosis admissions was found to be 23%.…”
Section: Discussionmentioning
confidence: 85%
“… 18 However, it is also stated that this study cannot clearly show the frequency of DKA in all newly diagnosed diabetics, as hospitalizations of wards or admissions with hyperglycemia were not evaluated. 18 In another study where the frequency of DKA was evaluated in the first year of the pandemic in Turkey compared to the previous year, the frequency of severe DKA among hyperglycemia, ketosis, and ketoacidosis admissions was found to be 23%. 19 …”
Section: Discussionmentioning
confidence: 85%
“…In a multicenter study conducted in Saudi Arabia during the COVID-19 pandemic period, no significant difference was found between the HbA1c values of newly diagnosed DMs and diagnosed T1DMs without DKA [ 17 ]. On the other hand, in a multi-center study from Turkiye, it is reported that the frequency of new onset of Turkiye 1 diabetes and severe cases among children was increased and the cause of the increased severe presentation might be related to restrictions related to the pandemic [ 23 ]. Similarly, in some recent studies, it was evaluated that higher HbA1c levels of DKA patients presenting with newly diagnosed T1DM were associated with delayed admission to the hospital due to COVID-19 and the length of insulin-free periods compared to patients with previously-diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Data about the prevalence of diabetic ketoacidosis (DKA) are much more concordant in the literature. Several cohort studies [ 91 , 93 , 98 , 102 , 106 , 123 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ] and two meta-analyses [ 114 , 164 ] report increases in DKA frequency and DKA severity at diagnosis among newly diagnosed T1D patients. A multicenter study, involving 13 national diabetes registries (Australia, Austria, Czechia, Denmark, Germany, Italy, Luxembourg, New Zealand, Norway, Slovenia, Sweden, the USA (Colorado), and Wales) compared the observed DKA prevalence in children and adolescents in 2020 and 2021 to predictions based on trends over the prepandemic years 2006–2019.…”
Section: Diabetesmentioning
confidence: 99%